Shape-stable MXene/sodium alginate/carbon nanotubes hybrid phase change material composites for efficient solar energy conversion and storage. (10th November 2022) - Ye, Xingyun; Ma, Yingjiao; Tian, Zhuoyue; Sun, Hanxue; Zhu, Zhaoqi; Li, Jiyan; Liang, Weidong; Li, An
Abstract: Photothermal energy conversion and storage though phase change materials (PCMs) composites is one of the ideal methods for the efficient utilization of solar energy which is regarded as the cleanest and most sustainable renewable energy. Herein, a series of Ti3 C2 -introduced PCMs composites were developed by melt-dipping method exploiting MXene/sodium alginate/carbon nanotubes (CNTs) hybrid aerogels as supporting materials and tetradecylamine (TDA) as the impregnated PCM. The utilization of MXene is to enhance the light absorption performance of PCM composites which has significantly improved their absorbance under an extremely high loading rate exceeding 91.0 wt%. This result contributed to a high photothermal energy conversion efficiency up to 84.95% and an excellent thermal energy storage density with a relatively high latent heat up to 217.8 kJ/kg. Notably, the hybrid TDA/aerogel composites also exhibited remarkable cycling and crystallinity stability; their melting enthalpy still maintain up to 192.0 kJ/kg after 300th thermal and cooling cycles. Additionally, the obtained PCM composites also possess marvelous mechanical property and enhanced thermal conductivity. The excellent comprehensive performance demonstrated that the resultant composites show great potential application in solar energy conversion and storage. Graphical abstract: This work reports a facile preparation of novel PCM composites using MXene/CNTs-introduced porous aerogels as supporting materials and TDA as impregnated PCM for efficient solar energy conversion and storage. The resulting composites exhibit a high photothermal energy conversion efficiency of up to 84.95% and high energy storage capacity of up to 217.8 kJ/kg. Notably, the latent heat of PCM composites still remain up to 192.0 kJ/kg after 300th cycles. Due to the above-mentioned merits, the resultant composites show great potential applications in solar energy conversion and storage. Image 1 Highlights: MXene/sodium alginate/carbon nanotubes based PCM composites are first reported. The latent heat of resultant composites was tested up to 217.8 kJ/kg. The prepared composites show a high photothermal conversion efficiency (84.95%). The composites remain a latent heat of up to 192.0 kJ/kg after 300 thermal cycles. The composites possess excellent mechanical property for practical application.